Brachial plexus avulsion induced changes in gut microbiota promotes pain related anxiety-like behavior in mice - Zhang, Jian-lei; Xian, Hang; Zhao, Rui; Luo, Ceng; Xie, Rou-gang; Tian, Tong; Cong, Rui (Frontiers in Neurology, 2023)
Introduction Brachial plexus avulsion (BPA) injury develops frequent and intense neuropathic pain, involving in both peripheral and central nervous systems. The incidence of anxiety or depression caused by BPA-induced neuropathic pain is high, but the underlying mechanism remains unclear. Methods We established a BPA mice model and assessed its negative emotions through behavioral tests. To further explore the role of the microbiota-gut-brain axis in the unique emotional behavior after BPA, we performed intestinal fecal 16s and metabolomics assays. Psychobiotics (PB) supplementation was administered to BPA mice to check the probiotics effects on BPA-induced anxiety behaviors. Results Pain related anxiety-like behavior was observed at the early stage after BPA (7 days), while no depression-like behavior was detected. Intriguingly, gut microbiota diversity was increased in BPA mice, and the most abundant probiotics, Lactobacillus, showed obvious changes. Lactobacillus_reuteri was significantly decreased in BPA mice. Metabolomics analysis showed that Lactobacillus_reuteri-related bile acid pathway and some neurotransmitter amino acids were significantly altered. Further PB (dominated by Lactobacillus_reuteri) supplementation could significantly relieve BPA-induced anxiety-like behaviors in mice. Conclusion Our study suggests that pathological neuralgia after BPA could alter intestinal microbiota diversity, especially Lactobacillus, and the changes in neurotransmitter amino acid metabolites may be the key reason for the onset of anxiety-like behaviors in BPA mice.